2012
DOI: 10.2967/jnumed.111.099325
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Global Myocardial Flow Dynamics Despite Normal Left Ventricular Function and Regional Perfusion in Chronic Kidney Disease: A Quantitative Analysis of Clinical 82Rb PET/CT Studies

Abstract: Impaired global myocardial flow reserve (MFR) may be associated with increased risk for cardiac events and coronary artery disease progression. Chronic kidney disease (CKD) is also considered a risk factor for cardiovascular disease. We sought to investigate the effect of CKD on the myocardial microcirculation in patients referred for clinical 82 Rb PET/CT, who had normal left ventricular (LV) function and no flow-limiting coronary artery disease. Methods: Estimated glomerular filtration rate (eGFR) was avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…Global MFR has also been studied in patients with renal insufficiency and was noted to be impaired in this population despite normal regional perfusion and left ventricle function. 21 To our knowledge, this is the first study to demonstrate reduced MFR using PET imaging in patients with HFpEF, extending and supporting recent work in this area. In this study, we showed that MFR was significantly lower in HFpEF than in controls, and more pronounced in HFpEF subjects with severe symptomatic HF (NYHA functional class 3-4).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Global MFR has also been studied in patients with renal insufficiency and was noted to be impaired in this population despite normal regional perfusion and left ventricle function. 21 To our knowledge, this is the first study to demonstrate reduced MFR using PET imaging in patients with HFpEF, extending and supporting recent work in this area. In this study, we showed that MFR was significantly lower in HFpEF than in controls, and more pronounced in HFpEF subjects with severe symptomatic HF (NYHA functional class 3-4).…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have demonstrated that MFR <2.0 is associated with a significant increase in the risk of cardiac events and death. 11,21,22 In addition to adding pathophysiologic insight into associations of HFpEF, the results of this study justify further research to determine if MFR may represent a novel prognostic risk factor for patients with HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been demonstrated that CKD induces a significant endothelial and microvascular dysfunction . The exact mechanisms by which coronary microcirculation is impaired in renal dysfunction are not fully elucidated . Neurohumoral activation, which is present in CKD, may be one contributor .…”
Section: Discussionmentioning
confidence: 99%
“…ADMA exerts opposite effects to those of nitric oxide, impairing endothelial function and vasodilatation . Arterial hypertension and chronic anemia, frequently associated with CKD, may also alter vasoreactivity . Despite uncertainties on the mechanism, it is clear that CKD patients have a reduced coronary vasodilator capacity .…”
Section: Discussionmentioning
confidence: 99%
“…104, 105, 114, 116 Reduced CFR has been also identified in patients with chronic kidney disease and CFR has been shown to have a significant positive correlation with GFR in these patients. 120 Additionally, global CFR was shown to be independently associated with all-cause mortality in dialysis dependent end stage renal disease patients. 121 Impaired CFR has been also described in a wide variety of chronic autoimmune diseases including rheumatoid arthritis, 122 systemic lupus erythematosus, 123 and systemic sclerosis.…”
Section: Quantification Of Flow With Radiotracer Imagingmentioning
confidence: 99%